The Influence of Financial Literacy of The Business Owners on Business Performance and Business Continuity of Coffee Shops in Semarang City - Nasya Zelika Haura; Widiartanto Widiartanto; Dinalestari Purbawati (Universitas Diponegoro, 2023)
Business in the coffee shop sector is groew2swwwqqqwing and developing, increasing coffee shops in various places, not least in Semarang City. They are often found in one location with two or more coffee shops with the same large business scale with more or less the same menu list. The type of research used in this study is explanatory research with the approach with a quantitative approach and processed using SmartPLS software. The research population includes all coffee shop business owners in Semarang, with 114 coffee shops. There were 90 samples with probability sampling with a simple random sampling approach. The result from this research are: that there is a positive and significant influence between financial literacy by business owners on business performance, there is an influence between business owners' financial literacy and business continuity at coffee shops in Java, and there is an influence between business performance and business continuity at coffee shops in Semarang. This research can be used to solve problems experienced by many business owners or as input and additional information for business owners that can be considered so that they can evaluate in order to improve their business performance and continuity. For instance, coffee shop owners need to broaden their information and connection since there are still more of them who need to be made aware of information about alternative sources of finance. The following research can expand the sample coverage to be more comprehensive and modify the model to become, or it can also be by increasing the range of measuring indicators.